2005
DOI: 10.1038/modpathol.3800373
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-specific cadherin, a specific marker for the distal portion of the nephron and related renal neoplasms

Abstract: Renal cell neoplasms are presumably derived from different cell types of the nephron. Clear cell and papillary renal cell carcinoma (RCC) are thought to be of proximal tubular origin, whereas oncocytoma and chromophobe RCC are derived from intercalated cells of distal nephron. A few molecules, such as RCC marker and CD10, have been shown to be markers for clear cell RCC and papillary RCC. Such markers are not yet available for renal tumors presumably of the distal nephron. The expression of kidney-specific (Ks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 17 publications
3
77
1
1
Order By: Relevance
“…17 Kidney-specific cadherin was found in one study to be almost exclusively expressed in chromophobe renal cell carcinoma, 34 however this finding was not supported by the others who found it also expressed in oncocytomas. 35 Similarly, cytokeratin 7 does not appear to show the consistent immunoreactivity in chromophobe renal cell carcinomas as suggested by some, preventing its utility for positive diagnostic differentiation from oncocytomas. 36 Inversely, RON proto-oncogene product and S100 protein were found preferentially expressed in oncocytoma warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Kidney-specific cadherin was found in one study to be almost exclusively expressed in chromophobe renal cell carcinoma, 34 however this finding was not supported by the others who found it also expressed in oncocytomas. 35 Similarly, cytokeratin 7 does not appear to show the consistent immunoreactivity in chromophobe renal cell carcinomas as suggested by some, preventing its utility for positive diagnostic differentiation from oncocytomas. 36 Inversely, RON proto-oncogene product and S100 protein were found preferentially expressed in oncocytoma warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38] Renal cell carcinoma marker antibody, CD10, glutathione S-transferase-a and others have shown specificity for clear cell renal cell carcinoma, 28,29 a-Methylacyl CoA racemase is expressed in papillary renal cell carcinoma, 30 whereas parvalbumin, b-defensin 1 and most recently KIT are used as markers for chromophobe renal cell carcinoma and oncocytoma. [31][32][33] However a marker with sufficient specificity to differentiate between chromophobe renal cell carcinoma and oncocytomas has not yet been unequivocally established.…”
Section: Discussionmentioning
confidence: 99%
“…7, blue diamonds). Another cadherin, Cdh16, is a marker of the distal tubule (Shen et al, 2005). Thirteen of the 58 RV cells expressed Cdh16 (Fig.…”
Section: Is the Rv Pre-patterned?mentioning
confidence: 99%
“…In RCC cultures, instead, about 93% of cells were CD13-positive and did not evidence any detectable signal for calbindin ( Figure 1A), in accord with the proximal tubular origin of RCCcc and RCCpap. 24 Moreover, primary cultures were analyzed for the expression of CA9, a powerful marker for RCC, which is known to be expressed in most, although not all, of the malignant clear cells, in a smaller number of papillary cells and is almost undetectable in normal renal cells. 25,26 Our tested RCC cultures were positive for CA9, and the FACS analysis showed that in RCC cultures an average of about 66% of cells were CA9-positive, whereas less than 2% of cells were positive in normal cortex cultures ( Figure 1A).…”
Section: Primary Culture Characterizationmentioning
confidence: 99%